Diffusion kinetics of boron in the X200CrMoV12 high-alloy steel (Journal of Mining and Metallurgy, Section B: Metallurgy, 2015)
In this work, the kinetics of formation of the boride layers (FeB/Fe2B), formed on the X200CrMoV12 steel used for the cold-working, was investigated. The boriding treatment was carried out in the powder mixture consisting of 5%B4C, 5% NaBF4 and 90% SiC. The boriding parameters are : 900, 950 and 1000°C with treatment times of 2, 4 and 6 h. The obtained borided layers (FeB/Fe2B) were characterized by the following experimental techniques: optical microscopy, scanning electron microscopy coupled to EDS analysis and XRD analysis. The kinetics of boron diffusion in the X200CrMoV12 steel was also studied. As a result, the time dependence of the borided layers thicknesses followed a growth parabolic law. The boron activation energy was estimated as 199.37 kJ mol-1 for the X200CrMoV12 steel. A full factorial design with 2 factors at 3 levels was employed to estimate the total boride layer thickness as a function of the boriding parameters (time and temperature) and a simple equation was proposed. Finally, an iso-thickness diagram was given as a tool to predict the total boride layers thicknesses in relation with the practical utilization of this kind of steel.